Combinations of nonprotein nitrogen and natural protein affect performance of finishing steers fed flaked corn diets - Healy, B.J.; Brandt, Robert T., Jr.; Eck, T.P. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Two hundred crossbred steers (7 85 lb) were used to evaluate the effects of the relative proportion of supplemental nitrogen derived from soybean meal (SBM) and urea. Treatments included an unsupplemented negative control and four 13% CP diets containing SBM:urea proportions (nitrogen basis) of 100:0, 67:33, 33: 67, and 0:100. Steers fed the control diets gained 38% slower (P<.01); ate 4% less feed (P<.10); were 33% less efficient (P<.01); and had lighter carcasses (P<.01) with less backfat (P<.01), less kidney, pelvic, and heart fat (KPH; P<.12), less ribeye area (REA; P<.11) , and less marbling (P<.01) than nitrogen-supplemented steers. Among steers fed supplemented diets, feed intake increased linearly as proportion of SBM increased (P<.01) . Daily gain (P<.05) and feed:gain (P<.05) responded quadratically and was best for steers fed combinations of the nitrogen sources. Similarly, hot carcass weights and backfat thickness were greater (P<.06) for steers fed the mixed supplements. There was a tendency for a linear increase in KPH as proportion of urea in the diet was increased (P<.14). Yield grade, ribeye area, and marbling were unaffected by SBM:urea proportions. In high-concentrate finishing diets, at least some of the supplemental nitrogen should be derived from a natural, degradable-protein source.
Keywords: Beef; Soybean meal; Urea; Finishing steers